2016
DOI: 10.1093/cid/ciw451
|View full text |Cite
|
Sign up to set email alerts
|

Universal Mask Usage for Reduction of Respiratory Viral Infections After Stem Cell Transplant: A Prospective Trial

Abstract: Background. Respiratory viral infections (RVIs) are frequent complications of hematopoietic stem cell transplant (HSCT). Surgical masks are a simple and inexpensive intervention that may reduce nosocomial spread.Methods. In this prospective single-center study, we instituted a universal surgical mask policy requiring all individuals with direct contact with HSCT patients to wear a surgical mask, regardless of symptoms or season. The primary endpoint was the incidence of RVIs in the mask period (2010-2014) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 30 publications
(55 reference statements)
1
48
0
4
Order By: Relevance
“…A flow diagram of the literature search and related screening process is shown in Figure 1. A total of 21 studies met our inclusion criteria [4, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], including 12 case-control studies, 6 cluster randomized trials, 2 retrospective studies, and 1 cohort study (Table 1)…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…A flow diagram of the literature search and related screening process is shown in Figure 1. A total of 21 studies met our inclusion criteria [4, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], including 12 case-control studies, 6 cluster randomized trials, 2 retrospective studies, and 1 cohort study (Table 1)…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…When caring for RSVpositive patients our staff wore surgical masks. Implementation of a universal surgical mask policy, whereby all staff in direct contact with patients wore a mask, led to a significant reduction in respiratory viral illness in a haemopoeitic stem cell unit [14].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis in paediatric outbreaks of RSV is well described; however, studies into its use in adults are lacking [14]. Prophylactic administration of palivizumab was administered during a nosocomial outbreak involving five stem cell transplant patients in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large single center study had reported a reduction of RVIs in their HSCT unit from 10.3% to 4.4% by mandating universal surgical masks for all individuals in direct contact with HSCT patients in addition to standard infection control precautions (7). Of note, almost all the reduction in RVIs came from reduced incidence of HPIV3 infections with no significant reductions in the incidence of influenza A, B and respiratory syncytial virus (RSV) infections.…”
Section: Discussionmentioning
confidence: 99%